Proximity to the Promoter and Terminator Regions Regulates the Transcription Enhancement Potential of an Intron - Dwyer, Katherine; Agarwal, Neha; Gega, Alisa; Ansari, Athar (Frontiers in Molecular Biosciences, 2021)
An evolutionarily conserved feature of introns is their ability to enhance expression of genes that harbor them. Introns have been shown to regulate gene expression at the transcription and post-transcription level. The general perception is that a promoter-proximal intron is most efficient in enhancing gene expression and the effect diminishes with the increase in distance from the promoter. Here we show that the intron regains its positive influence on gene expression when in proximity to the terminator. We inserted ACT1 intron into different positions within IMD4 and INO1 genes. Transcription Run-On (TRO) analysis revealed that the transcription of both IMD4 and INO1 was maximal in constructs with a promoter-proximal intron and decreased with the increase in distance of the intron from the promoter. However, activation was partially restored when the intron was placed close to the terminator. We previously demonstrated that the promoter-proximal intron stimulates transcription by affecting promoter directionality through gene looping-mediated recruitment of termination factors in the vicinity of the promoter region. Here we show that the terminator-proximal intron also enhances promoter directionality and results in compact gene architecture with the promoter and terminator regions in close physical proximity. Furthermore, we show that both the promoter and terminator-proximal introns facilitate assembly or stabilization of the preinitiation complex (PIC) on the promoter. On the basis of these findings, we propose that proximity to both the promoter and the terminator regions affects the transcription regulatory potential of an intron, and the terminator-proximal intron enhances transcription by affecting both the assembly of PIC and promoter directionality.